1973
DOI: 10.1002/macp.1973.021720124
|View full text |Cite
|
Sign up to set email alerts
|

New highly efficient initiators for the copolymerization of 1,3‐dioxolane with 1,3,5‐trioxane based on the derivatives of trifluoromethanesulfonic acid

Abstract: A successful initiator for the preparation of a copolymer of 1,3,5-trioxane (1) with 1,3-dioxolane (2) which is further designed for practical uses should not only be able to give sufficiently high polymerization rates and polymerization degrees but also produce a polymer with a low content of the unstable fraction. Although it is known that these parameters as well as the copolymer structure l ) (tendency of the formation of blocks) depend on the initiator used, the reasons of these dependences are not yet fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1974
1974
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…55,57 Triflic acid, belonging to the strongest acids, was used first in CROP a long time ago (1973), namely, in CROP of THF and cyclic acetals (the least basic among cyclic monomers). 86 Most probably TfOH is (or was) used (in ppm concentration) in industrial CROP of 1,3,5-trioxane, leading to the high molar mass thermoplastic polyacetal.…”
Section: Amm Polymerization Of Cyclic Esters Initiated With Protic Co...mentioning
confidence: 99%
“…55,57 Triflic acid, belonging to the strongest acids, was used first in CROP a long time ago (1973), namely, in CROP of THF and cyclic acetals (the least basic among cyclic monomers). 86 Most probably TfOH is (or was) used (in ppm concentration) in industrial CROP of 1,3,5-trioxane, leading to the high molar mass thermoplastic polyacetal.…”
Section: Amm Polymerization Of Cyclic Esters Initiated With Protic Co...mentioning
confidence: 99%
“…Penczek and coworkers 15 have shown that the best results, i. e., short induction periods, high polymerization rates, high degrees of polymerization and a low content of unstable fraction, comparable with other POM copolymers, have been obtained when TO was copolymerized with DO in the presence of the ester or anhydride derivatives of TFS. The excellent performance of these systems as cationic initiators was ascribed to the low nucleophilicity and stability of the CFaSOzoe anion.…”
Section: Resultsmentioning
confidence: 97%
“…Table VII shows a comparison of the results for the copolymerization of TO with DO in the presence of TFS, its anhydride or other types of cationic initiators. The copolymerizations 15 were conducted at 60°C in cyclohexane as the solvent and in the presence of 2.0 weight percent (sum of Table VII were carried out for three hours except for the one initiated with the triphenyl methylium salt (AsFs8 anion) which lasted for two and a half hours. The base stabilization of some copolymers was carried out in benzyl alcohol at 150°C in the presence of tri-n-butylamine for 30 min.…”
Section: Ch2mentioning
confidence: 99%
“…Penczek and Kubisa [17,18] have shown that in the presence of alcohols, the polymerization rate of epoxide monomers can undergo an acceleration effect. They have proposed an 'activated monomer mechanism'.…”
Section: Resultsmentioning
confidence: 99%